Water-soluble poly(p-aryleneethynylene)s: a sensor array discriminates aromatic carboxylic acids - Han, Jinsong; Wang, Benhua; Bender, Markus; Seehafer, Kai; Bunz, Uwe H. F. (ACS applied materials & interfaces, 2016)
A chemical tongue consisting of 11 elements (four poly(p-aryleneethynylene)s (PAE) at pH 7 and pH 13, and seven electrostatic complexes formed from oppositely charged poly(p-aryleneethynylene)s at pH 7) discriminate 21 benzoic and phenylacetic acid derivatives in aqueous solution. The mechanism of discrimination is the fluorescence modulation of the PAEs, leading to quenching or fluorescence turn-on. The PAEs alone at both pH values and the tongue, consisting of the complexes only, discriminate the 21 acids with 92% (PAEs at pH 7), 95% (PAEs at pH 13), and 99% (complexes at pH 7) reliability after linear discriminant analysis (LDA). A sensor field with all 14 elements, according to LDA, discriminates all of the 21 acids with 100% accuracy.